2019
DOI: 10.3390/app9122426
|View full text |Cite
|
Sign up to set email alerts
|

Wake Flow Characteristics over an Articulated Lorry Model with/without AC-DBD Plasma Actuation

Abstract: The wake flow characteristics of a 1:20 scale articulated lorry model with a linear Alternate Current Dielectric Barrier Discharge (AC-DBD) plasma actuation implemented was experimentally investigated. Time-averaged velocity, turbulence, and vorticity information along the centreline of the model were constructed using a two-component particle image velocimetry technique. In addition, force balance was used to measure the time-average drag force acting on the model with and without the use of AC-DBD plasma act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Whereas the related topic of plasma actuators (PA) for flow control applications is widely studied [9][10][11][12][13][14][15][16][17][18][19][20], there is recently a growing interest in the study of surface dielectric barrier discharges (SDBDs) as an anti-icing and de-icing system [21][22][23][24][25][26][27][28][29][30]. Probably Meng et al [24] and Cai Jinsheng et al [21] were the first who reported experimental results indicating that SDBDs can work as an anti/de-icing system.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the related topic of plasma actuators (PA) for flow control applications is widely studied [9][10][11][12][13][14][15][16][17][18][19][20], there is recently a growing interest in the study of surface dielectric barrier discharges (SDBDs) as an anti-icing and de-icing system [21][22][23][24][25][26][27][28][29][30]. Probably Meng et al [24] and Cai Jinsheng et al [21] were the first who reported experimental results indicating that SDBDs can work as an anti/de-icing system.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that a sudden change in wind speed near the bridge pylon is unfavorable for driving stability [18], and countermeasures have been explored for improving the wind environment at the bridge deck and ensuring driving safety [19,20]. Wind barriers, as an effective countermeasure, have had increasing attention from scholars [21][22][23]. Alonso-Estebanez et al [24] numerically studied and compared the aerodynamic coefficients of a truck on an embankment both with and without the wind fences installed.…”
Section: Introductionmentioning
confidence: 99%